2017
DOI: 10.1002/cne.24171
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of parvalbumin synapses in human dorsolateral prefrontal cortex

Abstract: Coordinated activity of neural circuitry in the primate dorsolateral prefrontal cortex (DLPFC) supports a range of cognitive functions. Altered DLPFC activation is implicated in a number of human psychiatric and neurological illnesses. Proper DLPFC activity is, in part, maintained by two populations of neurons containing the calcium-binding protein parvalbumin (PV): local inhibitory interneurons that form Type II synapses, and long-range glutamatergic inputs from the thalamus that form Type I synapses. Underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 136 publications
(219 reference statements)
3
8
0
Order By: Relevance
“…We observed that 74 ± 4.1% of presynaptic terminals contained MitoDendra+ mitochondria in control cells (Figure 2F, 2G). This is consistent with literature where approximately 75% of PV+ axonal boutons are enriched with mitochondria, and this is in contrast to pyramidal cells where less than half are associated with mitochondria (Glausier et al, 2017;Kwon et al, 2016;Smith et al, 2016;Vaccaro et al, 2017). However, we report a marked reduction in the axonal presynaptic terminals that contained mitochondria in the cells where Miro1 was knocked-out (51 ± 4.0%, Figure 2G, p = 0.003, unpaired t-test).…”
Section: Loss Of Miro1 In Parvalbumin Interneurons Results In Mitochondrial Clustering In the Soma And Depletion From Axonal Presynaptic supporting
confidence: 93%
“…We observed that 74 ± 4.1% of presynaptic terminals contained MitoDendra+ mitochondria in control cells (Figure 2F, 2G). This is consistent with literature where approximately 75% of PV+ axonal boutons are enriched with mitochondria, and this is in contrast to pyramidal cells where less than half are associated with mitochondria (Glausier et al, 2017;Kwon et al, 2016;Smith et al, 2016;Vaccaro et al, 2017). However, we report a marked reduction in the axonal presynaptic terminals that contained mitochondria in the cells where Miro1 was knocked-out (51 ± 4.0%, Figure 2G, p = 0.003, unpaired t-test).…”
Section: Loss Of Miro1 In Parvalbumin Interneurons Results In Mitochondrial Clustering In the Soma And Depletion From Axonal Presynaptic supporting
confidence: 93%
“…Electron microscopy (EM) provides nanometer resolution for ultrastructural identification of synaptic contacts and has been employed for brain-area and cell-type quantitative analysis (Bock et al, 2011; Briggman et al, 2011; Kim et al, 2014; Chandrasekaran et al, 2015); however, EM is hampered by technical demands of sample preparation, imaging time, data storage, and labor-intensive analysis that make comparisons across multiple individuals or conditions difficult. Recent studies have attempted to use EM for quantitative analysis of synapse organization between defined presynaptic and postsynaptic partners, but these computationally-intensive approaches are difficult to adopt and scale for broad use (Kubota et al, 2015; Glausier et al, 2017; Kornfeld et al, 2017; Vishwanathan et al, 2017). Fluorescence-based microscopy methods are an attractive alternative to EM, because light microscopy facilitates faster acquisition of larger tissue volumes and enables use of spectrally distinct, genetically encoded fluorophores for discrimination of molecularly diverse cells and synapse types.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, human postmortem brain samples can be associated with PMIs of hours to days, and perfusion-fixation of human brain is exceptionally rare. Despite these challenges, qualitative and quantitative EM studies of postmortem human brain tissue have been performed in immersion-fixed samples with PMIs ranging from 4 to 100 hr, 9,[10][11][12][13][14][15][16] though the presence of postsynaptic densities (PSD), myelin sheaths, and mitochondria appear to be the measures most resilient to extended PMIs. 9,[12][13][14][15]17 Moreover, other pre-and postmortem factors can affect tissue and ultrastructure quality other than PMI.…”
Section: Introductionmentioning
confidence: 99%